Gene Regulation Using Spherical Nucleic Acids to Treat Skin Disorders - Thomas R. Holmes; Amy S. Paller (MDPI AG, 2020)
Spherical nucleic acids (SNAs) are nanostructures consisting of nucleic acids in a spherical configuration, often around a nanoparticle core. SNAs are advantageous as gene-regulating agents compared to conventional gene therapy owing to their low toxicity, enhanced stability, uptake by virtually any cell, and ability to penetrate the epidermal barrier. In this review we: (i) describe the production, structure and properties of SNAs; (ii) detail the mechanism of SNA uptake in keratinocytes, regulated by scavenger receptors; and (iii) report how SNAs have been topically applied and intralesionally injected for skin disorders. Specialized SNAs called nanoflares can be topically applied for gene-based diagnosis (scar vs. normal tissue). Topical SNAs directed against TNFα and interleukin-17A receptor reversed psoriasis-like disease in mouse models and have been tested in Phase 1 human trials. Furthermore, SNAs targeting ganglioside GM3 synthase accelerate wound healing in diabetic mouse models. Most recently, SNAs targeting toll-like receptor 9 are being used in Phase 2 human trials via intratumoral injection to induce immune responses in Merkel cell and cutaneous squamous cell carcinoma. Overall, SNAs are a valuable tool in bench-top and clinical research, and their advantageous properties, including penetration into the epidermis after topical delivery, provide new opportunities for targeted therapies.